Legal Analysis of Authority in Determining Land Ownership for Catholic Religious Institutions under Minister of ATR/Head of BPN Regulation No. 5 of 2025: Study on Government Authority and Responsibility in Legal Perspective - Suhartoyo, Suhartoyo (Pelopor Publikasi Akademika, 2025)
This study analyzes the authority to determine land ownership rights for the Religious Body of the Catholic Church in Indonesia based on the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 5 of 2025 concerning the Determination of Land Rights. By using normative juridical law research methods. This study examines legal provisions and procedures related to the delegation of authority to determine land rights and land registration activities. The results of the study show that the Religious Body of the Catholic Church in Indonesia has the authority to own land titles by fulfilling the specified requirements and procedures. Regulation of the Minister of ATR/Head of BPN No. 5 of 2025 has significant juridical implications for the religious bodies of the Catholic Church in Indonesia, namely providing legal certainty and convenience for the Catholic Church Agency in obtaining land ownership rights through the authority of the Head of the Regional Office and the recommendation of the Land Office. In addition, the government is responsible for protecting and implementing land registration for Catholic Religious Legal Entities that have validity or legality based on existing laws and regulations. This research contributes to the understanding of the legal framework for the determination of land ownership for religious entities in Indonesia and its implications for religious activities and community services.